Analisis Dan Perancangan Sistem Informasi Pengiriman Kargo Untuk Perusahaan Ekspedisi Antar Pulau (Studi Kasus PT Abadi Mitra Andhika) - Fauzan Tolabi; Ismiarta Aknuranda; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT Abadi Mitra Andhika (AMA) is an inter-island expedition company established in 1997. Current conditions for information delivery of goods starts from the receipt of goods from the sender and the delivery of goods is done manually. The sender comes directly to PT Abadi Mitra Andika to deliver goods which will then be received and recorded by Sales using Microsoft Excel. If a customer requests item status, Sales will contact the Operations and Vendor door. From here, there is a delay in the process of tracking information and operations so that to overcome this problem, an inter-island cargo shipping expedition information system is needed. To build an inter-island freight forwarding system information system, analysis and design of the system is needed. System analysis and design uses the OOAD (Object Oriented Analysis and Design) approach and is described using UML (Unifed Modeling Language). This study produces modeling of current business processes and proposed business processes, system requirements analysis, system design and evaluation conducted by business process reviews, usage scenarios, useability scenarios using WEBUSE (Website Usability Evaluation) and matrix traceability. The evaluation results of the review process and matrix traceability show that the user path matches the flow in the use case specification and all requirements have a unique code that can be traced to the feature.